2021
DOI: 10.3390/hydrology8040149
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological and Hydraulic Flood Hazard Modeling in Poorly Gauged Catchments: An Analysis in Northern Italy

Abstract: Flood hazard is assessed for a watershed with scarce hydrological data in the lower plain of Northern Italy, where the current defense system is inadequate to protect a highly populated urban area located at a river confluence and crossed by numerous bridges. An integrated approach is adopted. Firstly, to overcome the scarcity of data, a regional flood frequency analysis is performed to derive synthetic design hydrographs, with an original approach to obtain the flow reduction curve from recorded water stages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The index-flood method is intended for regional flood frequency analysis [46,47]. This method combines data from several HSs to obtain one theoretical distribution function, i.e., regional growth curve, supposing an index (scaling factor) can be found at ungauged HS elsewhere or by some other method [17].…”
Section: Flood Information Transfermentioning
confidence: 99%
“…The index-flood method is intended for regional flood frequency analysis [46,47]. This method combines data from several HSs to obtain one theoretical distribution function, i.e., regional growth curve, supposing an index (scaling factor) can be found at ungauged HS elsewhere or by some other method [17].…”
Section: Flood Information Transfermentioning
confidence: 99%
“…To identify and mitigate these errors, SABER compares the bias-corrected flows against values that are statistically likely to determine if flow values seem reasonable. Specifically, SABER compares the distribution of corrected flows against a Gumbel Type 1 distribution, which is commonly used for estimating high-flow values [60][61][62]. SABER replaces flows with a return period of 100 years or larger with the 100-year discharge predicted by the Gumbel Type 1 distribution.…”
Section: Applying Corrections and Statistical Refinementsmentioning
confidence: 99%
“…Therefore, it was concluded that many of them influence the flood depth and the extent of flooded areas upstream of the bridges. The final results are the more important, the easier they are to be included in the design of road infrastructure and hydrotechnical builds for civil protection [15].…”
Section: Contributed Papersmentioning
confidence: 99%